The role of tropical abandoned land relative to ecological and economic aspects - Karmini Karmini; Karyati Karyati; Kusno Yuli Widiati (Forest and Society, 2020)
The floristic structure and composition of abandoned lands in the tropic have been observed to be changing dynamically during the succession process. This is mostly because they are not utilized maximally, therefore, there is a need to assess the economic and ecological impacts of this land abandonment in tropical areas. This study was conducted to determine the ecological aspects of standstructure, floristic composition, and species diversity and analyze the economic aspects of standing trees in tropical abandoned land. The vegetation containing woody trees with a diameter at breast height (DBH) of > 5 cm were surveyed at six subplots sized 20 m × 20 m. The economic parameters were evaluated using data of log price, logging cost, profit margin, and stumpage value of standing trees in the study plot and a total of 126 trees including 26 species of 25 genera of 18 families were recorded. The most common species found were Macaranga tanarius with 50.60%, Bridelia glauca with 49.13%, and Pterospermum javanicum with 29.05% based on Importance Value Index (IVi). Moreover, the diversity, dominance, evenness, and richness indices were 1.23, 0.09, 0.87, and 5.17 respectively while the total log price at the abandoned land was 1,462.02 USD m-3 with an average value of 56.23USD m-3. The total and mean values of logging costs were 1,212.24USD ha-1 and 46.62USD ha-1, respectively while the total profit margin of log selling was USD337.39m-3 at maximum with an average of 12.98 USD m-3. Furthermore, the average stumpage value was 83.05 USD ha-1 while the total was calculated to be 2,159.36 USD ha-1.These findings showed the utilization of abandoned lands with respect to ecology and economic aspects has the ability to increase community welfare and support the implementation of developmental programs in the country.